Laminar Forced Convection Heat Transfer over Staggered Circular Tube Banks: A CFD Approach - M., Ishak; Tahseen, Tahseen Ahmad; M. M., Rahman (Faculty Mechanical Engineering, UMP, 2013)
This paper presents the numerical study on the two-dimensional forced convection heat transfer for staggered tube banks in cross flow under incompressible, steady-state conditions. This system is solved on the body fitted coordinates (BFC) using the finite volume method (FVM) for the flow over a bundle of cylindrical tubes. The constant heat flux is imposed on the surface of the tubes as the thermal boundary condition. The type of the arrangement is considered a staggered of tubes. The longitudinal pitch to tube diameter ratios (ST/D) of 1.25, 1.5 and 2 are also considered. Reynolds numbers are varied from 25 to 250 and Prandtl number is taken as 0.71. Velocity field vectors, temperature contours and local and average Nusselt numbers were analysed in this paper. It can be seen that the predicted results are good agreements with previous experimental and numerical results. The obtained results show that the heat transfer rate increases with decreases of the step to the longitudinal tube diameter. The local heat transfer strongly depends on the Reynolds number. It tends to obtain the highest values at the surface opposite to the direction of flow. The heat transfer rate is insignificant in the areas of recycling.